2008
DOI: 10.1093/jnci/djn344
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Breast Cancer Among Younger Women in the United States

Abstract: Increases in the incidence of postmenopausal breast cancers have been linked to screening and menopausal hormone use, but younger women have received less attention. Thus, we analyzed trends in breast cancer incidence (N = 387 231) using the National Cancer Institute's Surveillance, Epidemiology, and End Results Program 13-Registry database (1992-2004). Whites had higher incidence rates than blacks after age 40 years, but the reverse was true among younger women (black-white crossover). Among younger women, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(166 citation statements)
references
References 25 publications
(11 reference statements)
8
150
2
6
Order By: Relevance
“…For example, a study based on SEER data from US found a comparable trend with an increase of 1.3% per year for the period 1992e2004, among white US women less than 40 years old [11]. The canton-specific data from Switzerland, however, has been less definitive.…”
Section: Findings In Context With the Literaturementioning
confidence: 99%
“…For example, a study based on SEER data from US found a comparable trend with an increase of 1.3% per year for the period 1992e2004, among white US women less than 40 years old [11]. The canton-specific data from Switzerland, however, has been less definitive.…”
Section: Findings In Context With the Literaturementioning
confidence: 99%
“…Women in their 20s and 30s should have a clinical breast exam (CBE) as part of a periodic (regular) health exam by a health professional, at least every 3 years. Breast cancer mortality in the United States has decreased as a result of increased screening (Brinton et al, 2008;American Cancer Society, 2009).…”
Section: The Effects Of Education Program On Knowledge and Intention mentioning
confidence: 99%
“…cancer in young women is low in developed countries (Brinton et al, 2008). However, the incidence of breast cancer among young women in the low risk population of the South Asian countries including Nepal is much higher (Pradhananga et al, 2009;Kakarala et al, 2010).…”
Section: Introductionmentioning
confidence: 99%